(untitled) (International Journal of Food and Nutritional Sciences, 2022)
West Bengal is called of the river of land and wetlands. Sola-pith handicraft is the agro-based handicraft. Sola plant is a Hydrophytes plant which generally grows barren in lakes, ponds, channels of paddy fields, flooded low land areas and marshy waterlogged areas. Shola plant grows mainly in the wet areas of eastern part of India i.e., West Bengal, Assam, Orissa and Deccan. Shola pith plant belongs to the family- Fabaceae or Leguminosae and Genus- Aeschynomene. Shola seeds commonly get germinating at the time of pre-monsoon when fields get moisture. Hidden seeds which remain deposited in the soil to get developing and take three months to become full grown plant. It has full blooming during the time, months of September-October. The sola pith plant is a valuable plant that handicraft makes from sola-pith which can be comparable as fine art crafts by it pretty gorgeous look and amazing skill of artisans. The importance of the shola pith handicrafts are the both cultural, heritage and economic impact in our country, now at present more than 50,000 artisans are engaged in this activities in the West Bengal. However, it is facing a lot of crucial Problems to the artisans such as shortest of inputs of the sola-pith products due to decreasing wetlands, ponds and other factors. This research study paper is mainly focus on the prospects and problems of the harvesting and sola-pith products. It has a vital role in the production of sola-pith product differ from cultivation to the finished product. It is an unorganized sector and it has no power to control prices but they exploited by the middlemen and other entrepreneurs or exporters. This traditional handicraft which is being practiced by the artisans of a particular community (Malakars) in the West Bengal. The present study paper is based on the secondary data and also this research paper highlights that the implication is looking forwarded to contribute knowledge for better harvesting and achievement for the sola-pith handicraft in the West Bengal